The immune response of the scallop Argopecten purpuratus is associated with changes in the host microbiota structure and diversity. Issue 91 (August 2019) - Muñoz, K.; Flores-Herrera, P.; Gonçalves, A.T.; Rojas, C.; Yáñez, C.; Mercado, L.; Brokordt, K.; Schmitt, P.
Abstract: All organisms live in close association with a variety of microorganisms called microbiota. Furthermore, several studies support a fundamental role of the microbiota on the host health and homeostasis. In this context, the aim of this work was to determine the structure and diversity of the microbiota associated with the scallop Argopecten purpuratus, and to assess changes in community composition and diversity during the host immune response. To do this, adult scallops were immune challenged and sampled after 24 and 48 h. Activation of the immune response was established by transcript overexpression of several scallop immune response genes in hemocytes and gills, and confirmed by protein detection of the antimicrobial peptide big defensin in gills of Vibrio -injected scallops at 24 h post-challenge. Then, the major bacterial community profile present in individual scallops was assessed by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA genes and dendrogram analyses, which indicated a clear clade differentiation of the bacterial communities noticeable at 48 h post-challenge. Finally, the microbiota structure and diversity from pools of scallops were characterized using 16S deep amplicon sequencing. The results revealed an overall modulation of the microbiota abundance and diversity according to scallop immune status, allowing for prediction of some changes in the functional potential of the microbial community. Overall, the present study showed that changes in the structure and diversity of bacterial communities associated with the scallop A. purpuratus are detected after the activation of the host immune response. Now, the relevance of microbial balance disruption in the immune capacity of the scallop remains to be elucidated. Highlights: Changes in the host microbiota was assessed during the scallop immune response. The immune response was verified by ApBD1gene and protein expression. DGGE analysis indicated a clear clade differentiation of the bacterial communities 48 h post challenge. 16S rDNA deep amplicon sequencing showed an overall modulation of the microbiota abundance and diversity.